Colonialismos nacionales en acción: Experiencias militares en Chaco boreal en vísperas de la guerra, 1920/1930 - Luc Capdevila (Nuevo mundo - Mundos Nuevos, 2013)
This study examines the special relationship established between militaries and Amerindians of the Chaco in the 1920s, through the paths of three officers assigned to explore the territory and prepare its colonization by the Paraguayan and Bolivian governments. The method consists in studying the life history of these soldiers, analyzing their sensitivities and observing their practices whereby they were able to circulate in the Chaco, and build relationships between native peoples and the State Republican. The objective through these biographical studies, is to provide a comparative approach to national forms of colonialism Republicans, who asserted in the Chaco Boreal before the war of 1932-1935.